91.5k views
5 votes
Solve by substitution -4x-y=-2,y=-4x+3​

User Anandhu
by
4.9k points

1 Answer

3 votes

Answer:

No solution

Explanation:

Substitution is done by substituting one equation into another. To begin solve one equation for a variable.

Substitute y=-4x+3​ into -4x-y=-2.

-4x -(-4x + 3) = -2

-4x + 4x - 3 = -2

-3=-2

This is a false statement and there is no variable present anymore. This means the equations have no solution.

User Zadr
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.